Quality evaluation vs. assessment of nursing care records - Książek, Janina; Wesołowska, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. Quality of nursing care evaluated on the basis of nursing care records can be analysed by means of scientific methods or by carrying out an evaluation process. Evaluation is understood as estimation, calculation of value (of a condition, process, product, activity result, program, etc.). The aim. The aim of the study is evaluating the quality of nursing care based on nursing care records. Material and methods. The analysed material constitute 573 care history evaluation forms of patients treated in the Academic Clinical Centre of the Medical University of Gdańsk between 2002 and 2005. Calculations were performed by means of statistical software package StatSoft, Inc (2005), STATISTICA (data analysis software system), version 7.1. www.statsoft.com and Microsoft Excel calculation sheet. The level of significance was established at p=0,05. The following statistical tests were used in the study: nonparameter ANOVA (Kruskal-Wallis ANOVA, Friedman ANOVA) Mann-Whitney U test. Results. The research results prove that the method of evaluating nursing care quality based on nursing care records analysis should be used in future as a routine procedure meant to improve the level of quality.